Management of Large Cell Neuroendocrine Carcinoma - Corbett, Virginia; Arnold, Susanne; Anthony, Lowell; Chauhan, Aman (Frontiers in Oncology, 2021)
Background: Large cell neuroendocrine carcinoma (LCNEC) is a rare, aggressive cancer with a dismal prognosis. The majority of cases occur in the lung and the gastrointestinal tract; however, it can occur throughout the body. Recently advances in the understanding of the molecular underpinnings of this disease have paved the way for additional novel promising therapies. This review will discuss the current best evidence for management of LCNEC and new directions in the classification and treatment of this rare disease. Methods: We performed a PubMed search for “Large cell neuroendocrine carcinoma” and “High grade neuroendocrine carcinoma.” All titles were screened for relevance to the management of LCNEC. Papers were included based on relevance to the management of LCNEC. Results: Papers were included reviewing both pulmonary and extra pulmonary LCNEC. We summarized the data driven best practices for the management of both early and advanced stage LCNEC. We describe emerging therapies with promising potential. Discussion: LCNEC are rare and aggressive neoplasms. In advanced disease, the historical regimen of platinum based therapy in combination with etoposide or irinotecan remains among the commonly used first line therapies, however for extra thoracic LCNEC regimens like FOLFOX, FOLFOIRI and CAPTEM can also be used. Further effective and safe treatment options are desperately needed. Recently, new advances including a new understanding of the genetic subcategories of LCNEC and immunotherapy agents may guide further treatments.